Heat and Mass Transfer in Cesium Evaporation from Graphite Surface in Argon - Bespala E. V. Evgeniy (Evgeny) Vladimirovich; Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Pavlyuk (Pavliuk) A. O. Aleksander Olegovich; Novoselov I. Yu. Ivan Yurievich (2017, 2017)
Title screen